Green Brand Awareness, Green Brand Trust Mediators Influence of Green Marketing on Green Purchase Intention - Murtiningsih, Dewi; Marlapa, Eri; Putra, Yananto Mihadi; Nur, Hifizzah (Jurnal Doktor Manajemen (JDM), 2025)
Objective: This study aims to explore the influence of green marketing on green purchase intention and the mediating role of green brand awareness and green brand trust.Method: A random sample of 187 respondents was sampled, and PLS analysis used.Results: Green marketing positively influences green purchase intention and green brand awareness. Green brand awareness mediates the relationship between green marketing and green purchase intention. However, green brand trust has no direct effect on green purchase intention and does not mediate the relationship.Novelty: This study focuses on the mediating role of green brand awareness and green brand trust.Contribution: These findings provide insights for marketers to focus on other aspects that can increase purchase intention.